Sejarah Perkembangan dan Kedudukan Bahasa Indonesia - Imsakia Tahir; Rahma Ashari Hamzah; Lilis Suryani; Siti Nurhalisa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Indonesian has a long historical journey as a means of communication as well as a symbol of national identity. This study discusses the dynamics of the development and position of Indonesian using the library research method. Library research used in this study can be in the form of books, articles and journals, which are based on various historical references and academic studies. Originating from the Malay language which has long functioned as a lingua franca in the Nusantara region, Indonesian was then inaugurated as a unifying language through the Youth Pledge in 1928 and was confirmed in the 1945 Constitution as the state language. The discussion also covers the important role of Indonesian in various sectors, such as the world of education, government bureaucracy, mass media, and the realm of technology. Based on the results of the literature review, it can be concluded that Indonesian plays a role not only as a means of communication, but also as an important element in the formation of national identity and the integration of a pluralistic society. This study emphasizes that the existence and function of Indonesian continue to develop in line with social change and progress.